Creative industries: development processes under contemporary conditions of globalization - Kontrimienė, Valerija; Melnikas, Borisas (Business, Management and Economics Engineering, 2017)
The article deals with the processes of developing creative industries under conditions of a growth in the worldwide economy and globalization, discloses the role of the sector of creative industries and shows its place in the system of the modern global economy. The paper presents a comparative analysis of theories and theoretical approaches intended for the sector of creative industries and its development as well as defines regularities and specificities characteristic of the development of creative industries. Particular attention is shifted on the growth and development of creative industries considering the current challenges of globalization and on the most important specificities of the developing sector in the context of the challenges of economic globalization. The paper examines the trends reflecting the place of the sector of creative industries in the economy of the modern world, including the tendencies indicating changes in the export of the products created in this sector. The article considers the issues of developing creative industries and reveals priorities of future research.